The Representation of Democracy in Islamic News Sites Voa-Islam and ArRahmah - Rahmawan, Detta; Adiprasetio, Justito; Janitra, Preciosa Alnashava (Jurnal The Messenger, 2018)
In Indonesia, various groups with Islamic ideology are emerging and often promoting the idea of Islamic Law to replace democratic concept. Some of these groups use various websites to deliver their ideology to the public and as a form of resistance to the mainstream news. This study uses framing analysis to reveal how Islamic news websites such as VOA-Islam and ArRahmah, portray the concept of democracy unilaterally, according to what they believe. Throug the analysis results that have been done, it is found that the sites frequently claim that democracy is fail system, because democracy is expensive system, creates political oligarchy, and against the teachings of Qur an. These Islamic news websites also frequent;y used information from anti-democratic organization members such as HTI (Hizbut-Tahrir Indonesia), as their primary sources. By contrasting the concept of democracy with Islamic values, this group offered narration that did not lead to healthy and productive discussion.